Zinbiel superalgebras and superbialgebras - Agrebaoui, Boujemaa; Basdouri, Imed; Eljoudi, Jebli Mohamed (Ukrains’kyi Matematychnyi Zhurnal, 2026)
UDC 512.5In the present paper, we propose and study a new structure of the Zinbiel superalgebras. Moreover, we define dual bimodules and matched pairs. In addition, we establish a relationship between the dual bimodules of Zinbiel superalgebras and the matched pairs of Lie speralgebras. Furthermore, we examine the Manin triples of Zinbiel superalgebras. Finally, we present the theorem that establishes the links between the matched pairs of Zinbiel superalgebras, the Zinbiel superbialgebras, and the matched pairs of subadjacent Lie superalgebras.